1999
DOI: 10.1103/physreva.60.2554
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions ofn-level systems and gauge theories

Abstract: We find a relationship between unitary transformations of the dynamics of quantum systems with time-dependent Hamiltonians and gauge theories. In particular, we show that the nonrelativistic dynamics of spin-1 2 particles in a magnetic field B i (t) can be formulated in a natural way as an SU (2) gauge theory, with the magnetic field B i (t) playing the role of the gauge potential A i . The present approach can also be applied to systems of n levels with time-dependent potentials, U (n) being the gauge group. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…The exact solutions and the geometric phase factor of the time-dependent spin model have been extensively investigated by many authors [12][13][14][15][16][17][18][19]. Bouchiat and Gibbons discussed the geometric phase for the spin-1 system [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact solutions and the geometric phase factor of the time-dependent spin model have been extensively investigated by many authors [12][13][14][15][16][17][18][19]. Bouchiat and Gibbons discussed the geometric phase for the spin-1 system [12].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical algebraic structure of a type of general case of spin model such as the time-dependent L − S coupled system has been investigated and a set of SU (N ) generators was constructed to linearize the Hamiltonian by Cen et al [15]. The relationship between the unitary transformations of the dynamics of quantum systems with time-dependent Hamiltonians and the gauge theories has been found by Montesinos et al [17]. They discussed the time evolution of the Heisenberg spin system and obtained the formally exact solutions of the Schrödinger equation in a time-dependent magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the present work is the fruit of a long series of discussions with Pierre Noyes. paper [27] also works with minimal coupling for the FeynmanDyson derivation. The first remark about the minimal coupling occurs in the original paper by Dyson [1], in the context of Poisson brackets.…”
Section: Dynamical Equations Generalize Gauge Theory and Curvature Omentioning
confidence: 99%
“…[8]. Other works [10,11,12] have provided new insights ino the Feynman's derivation of the Maxwell's equations. Recently [13], some of the authors embedded Feynman's derivation of the Maxwell's equation in the framework of noncommutative geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Although with this approach, a Lagrangian or Hamiltonian structure is unnecessary, Hojman and Shepley [3] showed that by using a Helmholtz inverse variational problem under certain conditions, an action can be associated to these Feynman commutation relations. The interpretation of the Feynman's derivation of Maxwell's equations has generated [3,4,5,6,7,8,9,10,11,12] a great interest among physicists. In particular, Tanimura [4] has generalized the Feynman's derivation in a Lorentz covariant form with a scalar time evolution parameter.…”
Section: Introductionmentioning
confidence: 99%